The Social Dynamics of Open Data - Francois van Schalkwyk (African Minds, 2017)
The Social Dynamics of Open Data is a collection of peer reviewed papers presented at the 2nd Open Data Research Symposium (ODRS) held in Madrid, Spain, on 5 October 2016. Research is critical to developing a more rigorous and fine-combed analysis not only of why open data is valuable, but how it is valuable and under what specific conditions. The objective of the Open Data Research Symposium and the subsequent collection of chapters published here is to build such a stronger evidence base. This base is essential to understanding what open data's impacts have been to date, and how positive impacts can be enabled and amplified. Consequently, common to the majority of chapters in this collection is the attempt by the authors to draw on existing scientific theories, and to apply them to open data to better explain the socially embedded dynamics that account for open data's successes and failures in contributing to a more equitable and just society. CONTENTS Chapter 1: Introduction: The state of open data and open data research by François van Schalkwyk & Stefaan G Verhulst Chapter 2: The challenges of institutionalising open government data: A historical perspective of Chile's OGD initiative and digital government institutions by Felipe González-Zapata & Richard Heeks Chapter 3: Beyond standards and regulations: Obstacles to local open government data initiatives in Italy and France by Federico Piovesan Chapter 4: Governance of open spatial data infrastructures in Europe by Glenn Vancauwenberghe & Bastiaan van Loenen Chapter 5: Beyond mere advocacy: CSOs and the role of intermediaries in Nigeria's open data ecosystem by Patrick Enaholo Chapter 6: Rethinking civil society organisations working in the freedom of information and open government data fields by Silvana Fumega Chapter 7: Open your data and will 'they' build it? A case of open data co-production in health service delivery by Fabrizio Scrollini Chapter 8: The relational impact of open data intermediation: Experience from Indonesia and the Philippines by Arthur Glenn Maail Chapter 9: Smart cities need to be open: The case of Jakarta, Indonesia by Michael P Caňares Chapter 10: Protecting privacy while releasing data: Strategies to maximise benefits and mitigate risks by Joel Gurin, Matt Rumsey, Audrey Ariss & Katherine Garcia